Architectural Forensics in Anonymous Monsters. (1st December 2016) - Murray, Shaun
Architecture is a crime if it does not involve environmental DNA and digital forensics to aid in the design of the building. Architectural Forensics in Anonymous Monsters is a chthonic zenoarchaeology that constructs new models of thinking through construction and physical construction with the earth. The anonymous monster could be the alternative contracting/constructing models and ideas that architects consider valuable and inherently fundamental for architecture – the scaffolding of thought and the scaffolding of buildings. This scaffolding could become the anonymous support structure that enables but also underpins the monster under construction. This article is a design project developed to a highly tuned theoretical standpoint on how technology alters consciousness for the individual and for society. With coined phrases such as 'reflexive architecture' to explore the collapse of the biological and information divides whilst has re-applied the term syncretism to explain our experience of multiple realities at once. Technology is a tool and a means for individuals to explore pre-conceptions of themselves, to enter separate realities and bring back information. A computer can therefore be likened to undertaking a similar role to that of a shaman in accessing different levels of consciousness. Building as a constructed reality.